The value of gene Xpert MTB / RIF, ADA, TB-DNA in the early diagnosis of TB meningitis: Xpert MTB / RIF, ADA, TB-DNA, and TB meningitis - Yang, Han; Li, Aifang; Zhang, Yongfeng; Yang, Yuanli (Cellular and Molecular Biology, 2023)
This study was to explore the expression and correlation between gene Xpert MTB / RIF, ADA, and TB-DNA in TB meningitis. For this purpose, we selected 102 patients in the TB meningitis progression diagnosed and treated in our hospital from January 2019 to December 2020, and another 100 patients in the non-TB meningitis group were selected for the control experiment. Two sets of CSF samples were taken to analyze the gene Xpert MTB / RIF positive rate and the correlation between the expression and the progression of tuberculous meningitis by testing the levels of ADA and TB-DNA in the patient body using an automatic biochemical analyzer. Research indicated that The levels of gene Xpert MTB / RIF, ADA, and TB-DNA in the non-tuberculous meningitis group were lower than those in the tuberculous meningitis group (P<0.05; Levels of gene Xpert MTB / RIF, ADA, and TB-DNA were higher (P<0.05) in patients with group III tuberculous meningitis compared with those under grades I-II tuberculous meningitis, and levels of gene Xpert MTB / RIF, ADA, and TB-DNA were higher (P<0.05) in patients with group VI tuberculous meningitis compared with group III tuberculous meningitis; Gene Xpert MTB / RIF, ADA, TB-DNA) as factors occurring in TB meningitis progression, and all three were associated (P<0.05) with TB meningitis progression; Gene Xpert MTB / RIF, ADA showed a positive correlation (r = 0.296, P = 0.002); Gene Xpert MTB / RIF, TB-DNA showed a positive correlation (r = 0.422, P = 0.001); ADA, TB-DNA showed a positive correlation (r = 0.366, P = 0.001). It was concluded that Gene X-Pert MTB / RIF, ADA, and TB-DNA showed high levels in TB meningitis progression, and as the disease worsened, all three showed a positive association in TB meningitis progression.